Local and landscape influences on the habitat occupancy of the endangered maned sloth Bradypus torquatus within fragmented landscapes - Santos, Paloma Marques (2016)
The transformation of natural landscapes in extensive anthropogenic areas has significantly affected ecological processes, and studies that evaluate such changes are essential for the definition of conservation strategies. In this study, we sought to identify the variables influencing the occupancy of Atlantic forest fragments by the endemic and endangered maned sloth. We selected 33 sampling stations, distributed at least 500 m apart throughout the municipality of Santa Maria de Jetiba-ES, Brazil. We sampled each station five times to verify the presence or absence of the species and to collect local variables. Using GIS tools, we defined a buffer of 200 m around each fragment and calculated the landscape metrics. After analysis of collinearity, we selected six variables - three local variables, two at patch level and one at landscape level - to assess their effect on the occupancy and detection probabilities. We selected models using AICc and calculated the weight of evidence and ratio of the models as well as the cumulative weight of each predictor variable. We detected the sloth in 48% of the stations. Its occupation was positively correlated to two variables on the local scale: Important Feeding Trees and Canopy height. Our results show that the maned sloth respond to fine local scale variables, but not to landscape structure. This is probably associated with the relatively high proportion of forest cover in the study area, but it also indicates the maned sloth flexibility to occupy fragmented landscape. Based on our results, we reinforce the unquestionable importance of local variables for species occupancy within fragmented landscapes, such as those related with the forest structure, and it is particularly important for strictly arboreal species. (C) 2016 Deutsche Gesellschaft fur Saugetierkunde. Published by Elsevier GmbH. All rights reserved.